ASAS KESEIMBANGAN TRANSAKSI DALAM HUKUM TRANSAKSI SYARIAH - Husaini Husaini (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2015)
The principle of balance (Mabda 'at-tawazun fi al-mu'awadhah) althoughin fact a rare balance between the parties in the transaction, but the Islamiccontract law remains stressed the need to balance it, a good balance between whatis given and what is received and the balance in bear the risk. The principle ofbalance in the transaction (between what is given with what is received) isreflected in the cancellation of a contract that is experiencing imbalances strikingachievement. The principle of balance in bearing the risk of the transaction isreflected in the prohibition against usury, in which the concept of riba onlydebtors who bear all risks of loss of business, while creditors are free at all andshould receive a certain percentage of their funds even when experiencingnegative returns.